2020
DOI: 10.1177/0266242619896266
|View full text |Cite
|
Sign up to set email alerts
|

New venture evolution of migrants under institutional voids: Lessons from Shonga Farms in Nigeria

Abstract: This article inductively builds theory on how transaction costs may be alleviated and institutional voids bridged in developing economies, based on the case study of successful migrant entrepreneurial involvement in Nigerian agriculture: Shonga Farms. We argue that the iterative process of building conditions of trust through long-term commitment, involvement of regional government, appropriate modes of financial contracts and the gradual transitioning of controlling interests to private actors are factors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…Institutional theory has been used to understand the behaviour of entrepreneurial ventures under adversity (Bowen and De Clercq, 2008;Webb et al, 2009). Institutional voids -the absence of specialised intermediaries, regulatory systems and contract-enforcing mechanisms in emerging markets -are an outcome of conflict and contradiction among local political, community and religious spheres (Mair et al, 2012) and hamper the implementation of business strategies (Mickiewicz and Olarewaju, 2020). Weak, fragile states with institutional voids provide conditions for market exclusion of vulnerable persons as existing rules of the game, such as corruption, inequality, ethnic persecution and limited property rights, limit access to and participation in markets.…”
Section: Macro-societal Entrepreneurship Researchmentioning
confidence: 99%
“…Institutional theory has been used to understand the behaviour of entrepreneurial ventures under adversity (Bowen and De Clercq, 2008;Webb et al, 2009). Institutional voids -the absence of specialised intermediaries, regulatory systems and contract-enforcing mechanisms in emerging markets -are an outcome of conflict and contradiction among local political, community and religious spheres (Mair et al, 2012) and hamper the implementation of business strategies (Mickiewicz and Olarewaju, 2020). Weak, fragile states with institutional voids provide conditions for market exclusion of vulnerable persons as existing rules of the game, such as corruption, inequality, ethnic persecution and limited property rights, limit access to and participation in markets.…”
Section: Macro-societal Entrepreneurship Researchmentioning
confidence: 99%
“…Specifically, they posited that "in societies characterized by more severe formal institutional voids, entrepreneurs can incur relatively high costs in gaining formal status but receive minimal benefits in return; and given minimal constraints imposed on pursuing more informal activities, entrepreneurs can create value for themselves with relatively less risk" (page 512). Mickiewicz and Olarewaju (2020) conducted a case study of a farm run by migrants in Nigeria and noticed that cost of doing business is higher when there is a lack of quality institutions. Anokhin and Wincent (2012) have used an indirect proxy measure of country governance (i.e., the stage of development) and found that it positively moderates the effect of start-up rates and innovation, suggesting it is easier to reap the benefits of entrepreneurship when country governance is of high quality.…”
Section: Country Governance and Entrepreneurship Activitymentioning
confidence: 99%
“…The literature advises that projects should be made specific and concrete to enhance the chances of success (Jamali & Mirshak, 2007; Olarewaju, 2019), as vague notions of responsibility can hinder development where there are institutional voids (Mickiewicz & Olarewaju, 2020). The vagueness in the way the budgetary allocations were phrased in this context allowed for flexibility in interpretation.…”
Section: Rule and Case Analysismentioning
confidence: 99%